Edukasi Cegah Stres Akademik Melalui Komunitas “Sharing is Caring” - Devi Savitri Effendy; Cinta Stevi Syela; Tirsa Ayudya M; Anika Nur Halisa; Nurhasnah Said; Hartati Bahar; Hariati Lestari; Rizki Eka Sakti Octaviani (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Academic stress is commonly experienced by university students, impacting their psychological condition and potentially affecting their eating patterns. High-intensity stress can worsen mental well-being, leading to irregular and unhealthy eating habits. Sharing is Caring is a program that provides indirect social support to stay connected and offer emotional and informational support, helping students alleviate academic stress. The program's target audience is active students from the public health faculty, particularly those in the nutrition study program. The Sharing is Caring program is conducted online, consisting of two main components: using WhatsApp as a channel to distribute posters with messages and educational content, and holding offline meetings with participants to provide education and engage in direct discussions. Participants responded positively to both the online sharing group and the offline meetings.